2021
DOI: 10.1002/slct.202102084
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Antioxidant Biphenyl Appended 1,2,3‐Triazoles as Potential Chemo‐Sensor for Sn2+ Ions: Excellent Selectivity and Low Detection Limit

Abstract: Designing of chemo-sensors is a new scope of intrigue among researchers. After inspecting the beneficial and harmful effects of Sn(II) metal ions in living species, 1,2,3-Triazole based chemo-sensor 4 a have been synthesized via click route. In the current article, literarily new 1,2,3-Triazoles (4 a-4 d) have been synthesized and identified via various spectroscopic means such as NMR( 1 H & 13 C), IR and mass spectrometry. Triazole 4 a was explored for recognition properties via absorption and emission spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The prepared solutions were diluted to obtain the required concentrations using the molarity equation C 1 V 1 = C 2 V 2 . The LOD was calculated using 3σ/ S , and 10σ/ S was used to calculate the limit of quantitation, where σ signifies the standard deviation of a blank and S signifies the slope of the linear equation. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prepared solutions were diluted to obtain the required concentrations using the molarity equation C 1 V 1 = C 2 V 2 . The LOD was calculated using 3σ/ S , and 10σ/ S was used to calculate the limit of quantitation, where σ signifies the standard deviation of a blank and S signifies the slope of the linear equation. , …”
Section: Resultsmentioning
confidence: 99%
“…The topology of 2 is exactly the same as that of 1. In compound 3, two different types of metal centers are present, along with a 14,16-c net with stoichiometry (14-c)4(16-c); a new 2-nodal net topology is observed with the Schlafli symbol {3 28 .4 49 .5 14 }4{3 32 .4 56 .5 32 }.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the mechanistic pathway for the quenching of the emission spectra of the Cd-MOF with ions, the classical Stern–Volmer equation for quenching ( F 0 / F = 1 + K SV , where F 0 and F are the fluorescence intensities of Cd-MOF in the absence and presence of the quencher, respectively) was applied . The limit of detection (3σ/ S ) and limit of quantitation (10σ/ S ) were calculated and compared with the appropriate and literature values, where σ represents the blank standard deviation and S represents the slope of the linear regression equation according to ref …”
Section: Methodsmentioning
confidence: 99%
“…Singh et al developed a triazole-containing probe 43 which showed a fluorometric response to Sn 2+ ions in methanol solution. 120 Initially, probe 43 displayed two absorption bands at 208 nm and 260 nm. The band at 208 nm displayed a hyperchromic shift after consecutive addition of Sn 2+ metal ions, whereas the band at 260 nm initially showed a hyperchromic shift, then a hypochromic shift, which was attributed to the electron density transfer between 43 and Sn 2+ .…”
Section: Chemosensors For Tin Ionsmentioning
confidence: 99%